SEMANTIC AND COMMUNICATIVE TRANSLATION IN CHRONICLE OF A BLOOD MERCHANT - Aiqing Wang (Jurnal Bahasa Lingua Scientia, 2021)
Yu Hua is a celebrated avant-garde, post-modernist writer in contemporary China, whose chefs-d’oeuvre are exemplified by To Live, Chronicle of a Blood Merchant and Brothers. The novel Chronicle of a Blood Merchant was composed in 1995 and rendered into English by Andrew F. Jones in 2003. In the English version, two translation approaches can be attested, viz. semantic translation and communicative translation, propounded by Peter Newmark. Similes, metaphors and sayings in Chronicle of a Blood Merchant are saliently translated in a literal and faithful manner, in accordance with semantic translation. Furthermore, the narrative abounds with political allusions that are rendered in line with semantic translation. In terms of communicative translation that tends to be free and idiomatic, it is embodied by linguistic culture, social culture and religious culture in the sense of Nida (1945). Nonetheless, there are instances of under-translation, which encapsulates the weakness of communicative translation.